PENGEMBANGAN MEDIA PUSPA (POP-UP BOOK SISTEM PENCERNAAN MANUSIA) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V DI SDN KRADENANREJO - Chilla Adis Violita; Saeful Mizan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is an important element in human life. One subject that can provide critical and scientific thinking skills is Ilmu Pengetahuan Alam dan Sosial (IPAS). Interviews conducted by researchers with fifth-grade teachers at SDN Kradenrejo revealed that there are still many obstacles in IPAS learning, one of which is that learning activities are still teacher-centered with a lecture model. Therefore, the researchers developed PUSPA (Pop Up Book Sistem Pencernaan Manusia) media using the ADDIE model, which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The development results showed the validity of the media from experts at 88% (very suitable), media experts at 92% (very suitable), and language experts at 85.7% (very suitable). The practicality test scored 97.14% and 96%. Meanwhile, the media effectiveness test yielded a normalized gain value (N-Gain) of 0.74, which falls into the high category.